ANALISIS PENGARUH HARGA DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PT. DMS TOUR AND TRAVEL - Haryono Haryono; Rr Endang Wahyuni; Danang Darunanto (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
The competition of transportation services has become tight due to the development of transportation technology. Therefore, travel business competition as partner of the transportion services could also be recognized by the increasing number of similar companies that offer travel services such as ticket sales selling services by giving competitive price and using online services. The research is using Case Study. The aim is to provide an overview of the background, characteristics and distinctive character of the cases. The type of approach and the researcher for one case conducts an intensive, in-depth, detailed and comprehensive analysis (Sugiono: 2008, 98). It was clear that the price, quality of service, and customer satisfaction go hand in hand. In other words, the higher the price and the quality of services will simultaneously increase the customer satisfaction.